2014
DOI: 10.1080/00103624.2013.867055
|View full text |Cite
|
Sign up to set email alerts
|

Antimony Accumulation in Wheat Seedlings Grown in Soil and Water

Abstract: The purposes of the research were (1) to estimate the ability of wheat Triticum aestivum L. to uptake antimony (Sb) from contaminated soil and water, (2) to study effects of Sb bioaccumulation on the plant development and distribution of macro-and trace elements in the plants, and (3) to compare uptake of Sb and some other elements by wheat seedlings grown in solid (soil) and liquid (water) media. Both soil-grown and water-grown plants were capable of accumulating large amounts of Sb. In roots, concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Abbreviations: C-control; Sb 2.5-2.5 mg kg −1 Sb; Sb 5-5 mg kg −1 Sb. Data are shown as means±SD (n=6) other important agricultural plants, like rice, wheat, or maize (He and Yang 1999;Pan et al 2011;Shtangeeva et al 2014;Vaculíková et al 2014). The present study showed that relatively low Sb concentration in the medium (5 mg kg −1 Sb) greatly influenced root and shoot biomass.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Abbreviations: C-control; Sb 2.5-2.5 mg kg −1 Sb; Sb 5-5 mg kg −1 Sb. Data are shown as means±SD (n=6) other important agricultural plants, like rice, wheat, or maize (He and Yang 1999;Pan et al 2011;Shtangeeva et al 2014;Vaculíková et al 2014). The present study showed that relatively low Sb concentration in the medium (5 mg kg −1 Sb) greatly influenced root and shoot biomass.…”
Section: Discussionmentioning
confidence: 95%
“…It was shown that plants are more efficient in taking up SbIII than SbV, although SbV was the predominant form of Sb in various plants, probably due to relative instability of trivalent Sb forms (Ren et al 2014;Tisarum et al 2014). Within the plants, Sb is mostly accumulated in roots (Feng et al 2009;Shtangeeva et al 2014;Tisarum et al 2014); however, opposite was also observed (Pan et al 2011). The sites of Sb accumulation within plant tissues are still not clear or may vary between the species; Feng et al (2011) found most of Sb accumulated in cytosol, while Ren et al (2014) found that in rice plants, most of Sb was accumulated in cell walls and less in organelles and cytosol.…”
Section: Introductionmentioning
confidence: 98%
“…If Sb absorption is high, toxicity problems result in reduced growth, impaired absorption of other mineral elements, slowed photosynthesis, development of oxidative stress, etc. [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, excess Sb in soil may also be a risk to the environment and human health (Filella et al 2007, Shotyk et al 2005, Xiao et al 2015. A series of studies on the uptake of Sb by wheat, oat, and rye was reported by Shtangeeva et al (Shtangeeva et al 2014a, Shtangeeva et al 2014b, Shtangeeva et al 2012a, Shtangeeva et al 2012b), thereby providing a foundation for understanding the plant uptake of Sb.…”
Section: Introductionmentioning
confidence: 99%